Inclusion complex formation between natural dye extracted from pitaya fruit skin and Î²-cyclodextrin : kinetic and thermodynamic study - Norasiha, Hamid (2011)
The purpose of this study is to investigate the kinetic and thermodynamic parameters of inclusion complex formation between the natural dye and Î²-cyclodextrin (Î²-CD). The natural dye was extracted from skin pitaya fruit by using water extraction. The kinetic and thermodynamic studies were carried out by using UV-Vis spectroscopy in liquid phase. Effects of pH value, concentration of Î²-CD, temperature and ionic strength on the inclusion interactions were studied to obtain the information about the mechanism of inclusion complex. From the experiment, the best conditions for the natural dye to encapsulate into the Î²-CD can be determined. The pH, concentration of Î²-CD and temperature were determined to be pH 5, 0.004M of concentration and temperature of 25oC, respectively. Formation constant with 1:1 molar ratio was calculated using the modified Benesi Hildebrand equation. The formation constant was determined in the varied temperature condition. The formation constant was decreased as temperature increased. During the time, the thermodynamic parameters which is changes of enthalpy (ÎHo), changes of entropy (ÎSo) and free Gibss energy (ÎGo) were determined. In order to identify the thermodynamic parameters, the Van Hoff equation and the Free Gibss energy were used. From the equation, the change of enthalpy (ÎHo) and the change of entropy (ÎSo) are about -3.22 kJ/mol and 50.40 kJ/mol, respectively. Based on the thermodynamic parameters results, the inclusion process was deduced to be an exothermic. Since the reaction was reversible, so the reaction of the inclusion complex formation can be concluded to be spontaneously in the forward direction. The solid inclusion complex of natural dye and Î²-CD prepared by co-precipitation method were characterized. The characterization consist four samples which are natural dye itself, pure substance of Î²-CD, physical mixture and also the inclusion complex in solid form. The Fourier Transform Infrared (FTIR) was applied to examine the functional group of the guest and host molecule in the inclusion. The morphology surface of the samples was observed under Scanning Electron Microscope (SEM). Powder X-Ray Diffractometer (PXRD) was used to investigate the crystalline structure in the samples. In order to identify the thermal analysis such as percentage weight loss due to the water molecules contents, decomposition temperature, exothermic or endothermic peak assigned, the Thermogravimetry Analysis (TGA) and Differential Scanning Calorimetry (DSC) were used. From TGA result, the percentage weight loss due to the water molecule content for natural dye, Î²-CD, physical mixture and solid inclusion are 8.56%, 9.23%, 14.23% and 29.89%, respectively. The decomposition temperature showed that the solid inclusion complex decompose at 300oC which is higher than natural dye and Î²-CD. It could be proved that the natural dye is included in the cavity since the solid inclusion complex decomposes after natural dye.